Analysing the Hadith al-ifk: integrating prophetic crisis management principles into modern digital communication - Abu Hassan, Muhammad Ikram; Mustarim, Muhsin; Zakaria, Nur Muhammad Amin; Norain, Muhammad Syahid; Rahim, Muhammad Nashrull Haqiem (Academic Inspired Network, 2025)
This study examines the values and lessons contained in the story of Hadith al-ifk, a significant event that tested the unity and resilience of the Muslim community during the time of Prophet Muhammad PBUH. In today’s digital era, the spread of slander and false information has become widespread, and principles such as tabayyun (verification) and ethical leadership, as outlined in the story, are often neglected. Using a qualitative approach and analysing classical sources including the Qur’an, authentic hadith, and sirah literature, this study explores the Prophet’s leadership strategies, the value of patience, and the importance of tabayyun in addressing social and communication challenges. Findings reveal that the Prophet’s crisis management model emphasizing consultation, justice, and emotional restraint remains relevant for resolving conflicts and strengthening community cohesion today. The study also highlights the crucial role of Islamic communication principles in preventing misinformation and promoting social harmony, especially in the age of social media. In conclusion, the story of hadith al-ifk offers enduring guidance for reinforcing unity and resilience within the Muslim ummah, in line with the maqāṣid al-Qur’an and the Sunnah of the Prophet Muhammad PBUH